Ekspresi Kreatif Cerita Pendek Siswa Kelas XI Multimedia SMK Arinda Palembang Sebagai Media Peningkatan Literasi - Novri Yanti; Margareta Andriani; Nur Attikah (Universitas Maritim AMNI Semarang, 2025)
This service activity is carried out by lecturers and students of the Indonesian Language Education study program with the aim of increasing interest in reading and students having the ability to construct a short story based on building elements, structure and rules. Creative expressions of short stories produced by class XI Multimedia students at Arinda Vocational School Palembang shows significant potential as a medium for increasing literacy. Through short story writing activities, students are not only able to develop writing skills, but also improve critical thinking skills, imagination, and appreciation of various forms of literary works. This method encourages students to more actively explore ideas and create work that is relevant to their experiences and interests. Thus, the use of short stories as a literacy learning medium has a positive impact on improving students’ overall literacy skills. The service method used is descriptive with a qualitative approach. After carrying out service, students are expected to have high creativity because they can present interesting stories based on their experience and imagination and are able to include intrinsic and extrinsic elements in the stories they create.